The Multiple Roles of Ascorbate in the Abiotic Stress Response of Plants: Antioxidant, Cofactor, and Regulator - Xiao, Minggang; Li, Zixuan; Zhu, Li; Wang, Jiayi; Zhang, Bo; Zheng, Fuyu; Zhao, Beiping; Zhang, Haiwen; Wang, Yujie; Zhang, Zhijin (Frontiers in Plant Science, 2021)
Abstract: Ascorbate (ASC) plays a critical role in both plant abiotic stress response and growth and development process. The antioxidant role of ASC has been well studied, but there are still several confusing questions about the function of ASC in the response of plants to abiotic stress. Higher ASC content can scavenge more reactive oxygen species (ROS) and is helpful for plant abiotic stress tolerance. But in some cases, increasing ASC content impairs plant abiotic stress tolerance. In contrast, inhibiting ASC synthesis or regeneration can enhance plant abiotic stress tolerance. This confusing phenomenon may be due to ASC playing different roles in the different stage or process of stress response in different cell region. Studies are usually focused on the antioxidant function of ASC, but ignored its other roles more or less in plant abiotic stress response. In fact, ACS also can act as a cofactor of phytohormone synthesis enzyme and the regulator of plant stress signaling. Therefore, ASC can not only play as an antioxidant to eliminate the oxidative damage, but also involve in regulating phytohormone synthesis and the actions of plant cell signaling to coordinate plant growth and development process to better adapt to the varying environment. The function of ASC in plant abiotic stress response is important and complex. So the detail role of ASC in plant abiotic stress response should be analyzed according to specific physiological process in specific organ and cell region. In this review, we will discuss the versatile roles of ASC in the response of plants to abiotic stresses as antioxidant, cofactor and regulator.